FUNGSI BADAN USAHA MILIK DESA (BUMDES) SEBAGAI UPAYA MEINGKATKAN PEREKONOMIAN DESA KALIWEDI KECAMATAN GONDANG, SRAGEN - Wulandari, Tiantia Bernica; Padmaningrum, Dwiningtyas; Winarno, Joko (Universitas Muhammadiyah Semarang, 2023)
Regions Indonesia strive to be the best to advance and develop each region. The development of each region needs to be carried out, one of the efforts made is through village entrepreneurship. Village entrepreneurship can be accommodated in BUMDes which is developed through village government and village communities. The formation of BUMDes can be a solution to problems in the economy of rural communities by optimizing the potential of the village. This study aims to describe the process of establishing BUMDes in Kaliwedi Village, analyze the function of BUMDes as an effort to improve the economy in Kaliwedi Village, and analyze the support for business aspects that exist in BUMDes in Kaliwedi Village. This research method uses qualitative methods with a descriptive analysis approach. Locations were chosen purposively or deliberately in Kaliwedi Village. The determination of informants was carried out purposively, as well as the use of source and method triangulation methods. The results of this study stated that the process of establishing BUMDes Karya Mandiri Kaliwedi Village in 2014 already had BUMDes but it was called LKD, in 2019 Kaliwedi Village registered LKD as BUMDes and incorporated as BUMDes Karya Mandiri. The functions of BUMDes Karya Mandiri according to Government Regulation No. 11 of 2021 have eight functions, namely: 1) Consolidation of village community goods and/service products; 2) Production of goods and/services; 3) Shelter, buyers, marketing of village community products; 4) Village community business incubation; 5) Stimulation and dynamics of village community economic enterprises; 6) Services for basic and general needs for village communities; 7) Increasing the benefits and economic value of cultural wealth, religiosity and natural resources; and 8) Increasing the added value of village assets and village original income. The supporting aspects of BUMDes in realizing this function are: Natural Resources, Human Resources and Capital.